PHGDH Is Upregulated at Translational Level and Implicated in Platin-Resistant in Ovarian Cancer Cells - Bi, Fangfang; An, Yuanyuan; Sun, Tianshui; You, Yue; Yang, Qing (Frontiers in Oncology, 2021)
Background: Platinum-based chemotherapy is the first line option for ovarian cancer. The development of resistance to such chemotherapy results in treatment failure, while the underlying mechanisms are poorly understood. Methods: Clinical samples were collected from Shengjing hospital of China Medical University. MTT assay was used to see the proliferation and chemoresistance of ovarian cancer cells. Transwell migration and Matrigel invasion assays was used to see the invasion ability of ovarian cancer cells. In addition, Polysome profiling and Tissue microarray and immunohistochemical staining were also used. The statistical significance of the difference was analyzed by ANOVA and post hoc Dunnett’s test. Results: PHGDH is the first enzyme responsible for serine biosynthesis pathway. The current study demonstrated that PHGDH is upregulated in platin-resistant ovarian cancer cells and tissues at the protein level. Importantly, knockdown of PHGDH suppressed, while overexpression of PHGDH increased the survival upon cisplatin exposure, invasiveness and spheroid formation of ovarian cancer cells. The current study demonstrated that PHGDH translation was upregulated in platin-resistant ovarian cancer. In addition, our study provided evidence that LncRNA RMRP (RNA Component of Mitochondrial RNA Processing Endoribonuclease) was upregulated in platin-resistant ovarian cancer, which promoted enrichment of RNA binding protein DDX3X (DEAD-Box Helicase 3 X-Linked) on the PHGDH mRNA to promote its translation. Conclusion: Collectively, the current study described that PHGDH was upregulated and conferred resistance of ovarian cancer cells to cisplatin, suggesting that cisplatin resistance could be overcome by targeting PHGDH. Our study also provided evidence that differential PHGDH protein expression was defined by its translation, and RNA binding protein DDX3X and LncRNA RMRP are regulators of its translation.